The response of Tampa Bay to a legacy mining nutrient release in the year following the event - Morrison, Elise S.; Phlips, Edward; Badylak, Susan; Chappel, Amanda R.; Altieri, Andrew H.; Osborne, Todd Z.; Tomasko, David; Beck, Marcus W.; Sherwood, Edward (Frontiers in Ecology and Evolution, 2023)
Cultural eutrophication threatens numerous ecological and economical resources of Florida’s coastal ecosystems, such as beaches, mangroves, and seagrasses. In April 2021, an infrastructure failure at the retired Piney Point phosphorus mining retention reservoir garnered national attention, as 814 million liters of nutrient rich water were released into Tampa Bay, Florida over 10 days. The release of nitrogen and phosphorus-rich water into Tampa Bay – a region that had been known as a restoration success story since the 1990s – has highlighted the potential for unexpected challenges for coastal nutrient management. For a year after the release, we sampled bi-weekly at four sites to monitor changes in nutrients, stable isotopes, and phytoplankton communities, complemented with continuous monitoring by multiparameter sondes. Our data complement the synthesis efforts of regional partners, the Tampa Bay and Sarasota Bay Estuary Programs, to better understand the effects of anthropogenic nutrients on estuarine health. Phytoplankton community structure indicated an initial diatom bloom that dissipated by the end of April 2021. In the summer, the bay was dominated by Karenia brevis, with conditions improving into the fall. To determine if there was a unique carbon (C) and nitrogen (N) signature of the discharge water, stable isotope values of carbon (δ13C) and nitrogen (δ15N) were analyzed in suspended particulate material (SPM). The δ15N values of the discharge SPM were -17.88‰ ± 0.76, which is exceptionally low and was unique relative to other nutrient sources in the region. In May and early June of 2021, all sites exhibited a decline in the δ15N values of SPM, suggesting that discharged N was incorporated into SPM after the event. The occurrence of very low δ15N values at the reference site, on the Gulf Coast outside of the Bay, indicates that some of the discharge was transported outside of Tampa Bay. This work illustrates the need for comprehensive nutrient management strategies to assess and manage the full range of consequences associated with anthropogenic nutrient inputs into coastal ecosystems. Ongoing and anticipated impacts of climate change – such as increasing tropical storm intensity, temperatures, rainfall, and sea level rise – will exacerbate this need.